2016
DOI: 10.1111/gcbb.12308
|View full text |Cite
|
Sign up to set email alerts
|

Full carbon and greenhouse gas balances of fertilized and nonfertilized reed canary grass cultivations on an abandoned peat extraction area in a dry year

Abstract: Bioenergy crop cultivation on former peat extraction areas is a potential after-use option that provides a source of renewable energy while mitigating climate change through enhanced carbon (C) sequestration. This study investigated the full C and greenhouse gas (GHG) balances of fertilized (RCG-F) and nonfertilized (RCG-C) reed canary grass (RCG; Phalaris arundinacea) cultivation compared to bare peat (BP) soil within an abandoned peat extraction area in western Estonia during a dry year. Vegetation sampling,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 63 publications
(123 reference statements)
1
15
0
1
Order By: Relevance
“…Here R eco is modeled with an exponential temperature response curve fitted to the nighttime NEE fluxes. For LAV, R eco was directly measured with opaque chambers (Järveoja, Peichl, Maddison, Teemusk, & Mander, 2016).…”
Section: Measurements Of Net Ecosystem Co 2 Exchange and Auxiliary mentioning
confidence: 99%
“…Here R eco is modeled with an exponential temperature response curve fitted to the nighttime NEE fluxes. For LAV, R eco was directly measured with opaque chambers (Järveoja, Peichl, Maddison, Teemusk, & Mander, 2016).…”
Section: Measurements Of Net Ecosystem Co 2 Exchange and Auxiliary mentioning
confidence: 99%
“…This total, however, also included dark respiration of plants. Heterotrophic respiration from bare peat in a Finnish study was much lower: 1.8 Mg CO 2 ha −1 year −1 (Järveoja, Peichl, Maddison, Teemusk, & Mander, ),…”
Section: Discussionmentioning
confidence: 98%
“…The GPP model including RVI as biomass proxy was previously presented by Kandel et al . () and successfully adapted in other studies (Järveoja et al ., ; Karki et al ., ). In the current study, the GPP model was extended with a temperature function (Ft) in analogy to the commonly used approach to describe the effect of low temperatures on radiation use efficiency of C 3 crops (Andersen et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Järveoja et al . () reported that fertilizer application in RCG cultivated on peat soil increased biomass production, gross primary production (GPP) and the ratio of autotrophic to heterotrophic respiration. In contrast, only little is known about how improved agronomical managements such as harvest frequency can improve CO 2 uptake and yield of festulolium and tall fescue and thereby improve the GHG balance of these bioenergy crops.…”
Section: Introductionmentioning
confidence: 99%